2020
DOI: 10.1007/s10570-020-03068-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel supra coarse-grained model for cellulose

Abstract: Cellulose being the most widely available biopolymer on Earth is attracting significant interest from the industry and research communities. While molecular simulations can be used to understand fundamental aspects of cellulose nanocrystal selfassembly, a model that can perform on the experimental scale is currently missing. In our study we develop a supra coarse-grained (sCG) model of cellulose nanocrystal which aims to bridge the gap between molecular simulations and experiments. The sCG model is based on at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 90 publications
5
49
0
Order By: Relevance
“…Nowadays, atomistic modeling of cellulose nanocrystals has been used to complement experimental measurements. Computer simulations help to predict self-assembly as well as mechanical, energetic, thermal, and structural features of cellulosic nanomaterials and provide a fundamental understanding of the atomic-scale origins of these characteristics [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Models have been employed to predict some CNC properties including the most frequently reported mechanical ones [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, atomistic modeling of cellulose nanocrystals has been used to complement experimental measurements. Computer simulations help to predict self-assembly as well as mechanical, energetic, thermal, and structural features of cellulosic nanomaterials and provide a fundamental understanding of the atomic-scale origins of these characteristics [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Models have been employed to predict some CNC properties including the most frequently reported mechanical ones [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This value of modulus obtained using the modified AA-OPLS force field for carbohydrates was a bit higher as compared to the previously achieved values using previously simulated values as in [46]. The average chain length of the cellulose nanocrystals found in real life wood samples are of the order 100-200 nm and to this end, a supra coarse-grained MD approach for estimating cellulose mechanical properties was developed by Mehandzhiyski et al [48]. This coarse-grained approach was based on atomistic molecular dynamics simulations and was developed with the force matching coarse-graining procedure.…”
Section: Figure 24mentioning
confidence: 65%
“…and are the reference and predicted force acting on the i th atom in the l th configuration, respectively, and depends on the set of M parameters; N is the number of atoms in the atomistic MD configuration and L = 5000 is the total number of atomic configurations used in the fit. The average chain length of the cellulose nanocrystals found in real life wood samples are of the order 100-200 nm and to this end, a supra coarse-grained MD approach for estimating cellulose mechanical properties was developed by Mehandzhiyski et al [48]. This coarse-grained approach was based on atomistic molecular dynamics simulations and was developed with the force matching coarse-graining procedure.…”
Section: Figure 24mentioning
confidence: 99%
“…We believe that we extracted uniform trends that are common to all models with different torsion numbers, although some results for the model with large torsion number included the effect automatic settings such as the mesh segmentation method by the COMSOL software. While it has been reported that coarse-grained MD can simulate models with lengths as long as 1200 nm 22 , our finite element calculations have a significant advantage in dealing with lengths until 25-round twists (corresponding to 5800 nm) in tensile tests and 14 round twists (corresponding to 3248 nm) in bending tests, and we have succeeded in clarifying the irregular characteristic of pure torsional structures that do not take into account the atomic information. The characteristic mechanical responsiveness derived from the torsional structure revealed in this study could be useful for more precise analysis and characterisation of complex biological tissues and highly sophisticated functional materials.…”
Section: Discussionmentioning
confidence: 96%
“…Previously, the twisted structure of cellulose nanocrystals has been mainly predicted through molecular dynamics (MD) simulations 16 18 . The origin of the twist is attributed to the intramolecular and intermolecular hydrogen bonds 19 , van der Waals interactions 20 , cross-sectional area or diameter of the crystals 16 , 21 , 22 , and spontaneous twisting of the molecular chain sheets 23 , 24 . A MD/density functional theory (DFT) study revealed that crystal models of cellulose I exhibit a larger amount of twisting than other polymorphs, suggesting that cellulose II crystals are difficult to twist 23 .…”
Section: Introductionmentioning
confidence: 99%